(untitled) (Innovaciones Educativas, 2021)
In the present study, we examine the Argentinean higher education professors’ profiles and opinions regarding their context, the tools and the activities they use in their lessons, and the emotions they experience while teaching remotely. All that as a result of the suspension of face-to-face classes due to the preventive and mandatory social distancing measures because of COVID-19. A qualitative methodology with a descriptive correlational scope was applied along with univariate and multivariate analysis strategies. In order to collect the data, an online questionnaire was provided to a group of university and college professors with nationwide representation. The outcomes demonstrate a differentiated impact in topics regarding the tools they use and the emotions they experience during remote classes in the youngest group of professors compared to those with more experience. The aforesaid shows the need for a set of macro and micro educational policies to follow up the change of scenery to generate spaces as well as material and symbolic conditions that will allow the effective development of tasks in this context.